(untitled) (Research, Society and Development, 2022)
Objective: To present the stages of speech therapy as proposal for a program for health care for children and adolescents with Cleft Lip and Palate. Methods: Report of experience of the performance of academics and graduate students in an extension project aimed at the care of children and teenagers with Cleft Lip and Palate. Results: Speech-language pathology actions were presented that take place according to the age group of the individual were presented (0-12 months; 12-24 months; 24-48 months; 48 months - 18 years). The assessment of orofacial motricity, speech, swallowing, neuropsychological development and hearing is present at all stages of the program, so that altered functions can be qualified and rehabilitated early. Conclusions: this study demonstrated the importance of extension programs and speech-language pathology follow-up for the health care of children with clefts in the beginning of life up to 18 years of age. In addition, the activities of the extension project contributed to the knowledge of academics and speech-language pathology professionals about cleft.